Sentinel plants enable quantitative monitoring of bioavailable nitrate in soils and microbial environments - Eugene Li; Chiara Berruto; Tufan M. Oz; Elisa Grillo; Catherine Griffin; Yunqing Wang; Kimberley T. Muchenje; Jolie W. Jones; Gozde S. Demirer (Proceedings of the National Academy of Sciences, 2026)
Microbial transformations of nitrogen in soils strongly influence plant nutrition and ecosystem function, yet monitoring these processes remains challenging. Existing approaches rely largely on extraction-based laboratory assays, limiting the ability to track nitrogen dynamics in situ. Here, we engineer “sentinel plants,” genetically encoded plant biosensors that convert nitrate perception into a quantitative signal reporting plant-accessible nitrate. The sensor uses a synthetic nitrate-responsive promoter to drive a ratiometric luciferase reporter, enabling high-dynamic-range measurements. Sentinel plants exhibited a dose-dependent, reversible nitrate response with high specificity over alternative nitrogen sources. In agricultural soils from multiple California field sites, sensor output tracked analytically measured nitrate levels and resolved incremental nitrate amendments, reporting plant-accessible nitrate in complex soil matrices. Beyond environmental sensing, sentinel plants detected microbially generated nitrate in both liquid culture and a model soil. Using this platform, we characterized a minimal three-member microbial consortium that converted atmospheric nitrogen into plant-available nitrate via sequential nitrogen fixation and nitrification. This consortium increased tissue nitrate accumulation and plant fresh weight, demonstrating that sentinel plants can both monitor nitrate availability and characterize microbial communities that enhance plant growth.